Digital Culture and Language Change: The Role Of Social Media in Shaping Modern Communication In Kazakhstan, Monaco, and Indonesia - David Crystal; Mary Orr; Jan Blommaert (Proceeding of the International Conference on Language, Literature, and Culture Studies, 2024)
This paper investigates the impact of social media platforms on language usage and communication patterns in Kazakhstan, Monaco, and Indonesia. With the rise of digital platforms, language is constantly evolving, and new linguistic trends are emerging. The study looks at the interplay between online communication, youth culture, and the blending of languages, focusing on how social media serves as a medium for linguistic innovation and cultural expression in these three countries.